2021
DOI: 10.1111/bcp.15143
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events of alpelisib: A postmarketing study of the World Health Organization pharmacovigilance database

Abstract: Disproportionality analysis by information components (ICs) were used to evaluate the potential association between adverse events (AEs) and alpelisib.Results: A total of 33 327 reports were extracted, 5695 of them were chosen with alpelisib as the suspected drug. After combining the same ID, 687 cases remained. The 45-64-years group had the most cases (n = 203, 29.55%). There were 129 Preferred Terms with significant signals. Hyperglycaemia (IC025 = 6.74), breast cancer metastatic (IC025 = 5.85) and metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…20 In general, the toxicity profile was in line with previous reports. 12,[19][20][21][22][23] In this study, alpelisib showed hyperglycemia (61.9%), which is similar to the incidence in the SOLAR-1 trial. 22 Diarrhea (62.5%) and acneiform skin rash (3.13%), which are commonly observed in EGFR tyrosine kinase inhibitors, were the most common AEs in poziotinib.…”
Section: Discussionsupporting
confidence: 82%
“…20 In general, the toxicity profile was in line with previous reports. 12,[19][20][21][22][23] In this study, alpelisib showed hyperglycemia (61.9%), which is similar to the incidence in the SOLAR-1 trial. 22 Diarrhea (62.5%) and acneiform skin rash (3.13%), which are commonly observed in EGFR tyrosine kinase inhibitors, were the most common AEs in poziotinib.…”
Section: Discussionsupporting
confidence: 82%
“…According to disproportionality analysis, the most common signals at the SOC level were gastrointestinal disorders, general disorders and administration site conditions, metabolism and nutrition disorders, skin and subcutaneous tissue disorders, investigations and neoplasms benign, malignant and unspecified (incl cysts and polyps). The occurrence of the above SOCs was also confirmed in CHEN et al [ 21 ]. This is consistent with our results.…”
Section: Discussionsupporting
confidence: 71%
“…In 2021, Chen et al studied the AEs of alpelisib based on this database of VigiBase database. In our study, a total of 5, 647 patients of AEs of alpelisib were retained from 2019 to 2022, while CHEN et al reported only 687 cases from 2019 to 2021 [ 21 ]. Notably our report presented a more accurate and detailed description of alpelisib AEs, with the disproportionality analysis and an assessment of time to onset of AEs.…”
Section: Discussionmentioning
confidence: 75%
“…Our study expands upon the rapidly accumulating reports of real-world experience with alpelisib outside a clinical trial (12)(13)(14)(15)(16)(17)(18). We report a low ORR to alpelisib at 12.5% in a cohort of heavily pretreated patients with a median of 3 lines of prior treatment including chemotherapy, with rather a brief duration of response with a median of 5.77 months.…”
Section: Discussionmentioning
confidence: 67%